Chromatographic analysis of hazardous compounds in frying oils - Albuquerque, T.G. (2016)
In the last years, there was an increase in the consumption of pre-fried and fried foods, which leads to high intake of fats and oils subjected to thermal treatment. The oils and fats are usually processed to improve the quality, stability and safety. Despite removing a large amount of impurities from the oil, the processing can often originate the formation of contaminants that can cause additional health hazards to those who consume these foods. During processing, oils and foods are exposed to several factors that originate toxic compounds, namely 3-chloropropane-1,2-diol (3-MCPD), 4-hydroxy-2-nonenal (HNE) and 4-hydroxy-2-(E)-hexenal (HHE). 3-MCPD is a food processing contaminant included in the group of compounds known as chloropropanols, which is formed when fat and salt containing foods are processed at high temperatures. The Scientific Committee on Food has set a tolerable daily intake of 2 µg/kg of body weight, and has concluded that 3-MCPD is a non-genotoxic carcinogen for humans. HNE is a secondary lipid peroxidation product derived from the oxidation of n-6 PUFA, namely linoleic acid. HHE is formed by the oxidation of n-3 PUFA, namely docosahexaenoic and eicosapentaenoic fatty acids. It is of utmost importance to increase the safety of fried products by improving vegetable oils quality and performance. Due to the importance of this subject, the European Commission and the European Food Safety Authority established it as a priority to investigate, and considered that validated, reliable and accurate analytical methods for the analysis and quantification of these toxic compounds in oils, as well as mitigation strategies for its formation are needed. This paper brings an overview of existing data, health effects and analytical methods regarding the content of these compounds in oils/fats subjected to frying conditions, with and without food.